2003
DOI: 10.4269/ajtmh.2003.68.48
|View full text |Cite
|
Sign up to set email alerts
|

INCREASED APOPTOSIS AND EXPRESSION OF TUMOR NECROSIS FACTOR-α CAUSED BY INFECTION OF CULTURED HUMAN MONOCYTES WITH DENGUE VIRUS

Abstract: Dengue (DEN) virus is responsible for one of the most significant viral diseases in tropical countries. Monocytes/macrophages (Mo/M) are the major target cells for DEN virus. To determine the effects of the interaction between DEN virus and Mo/M, human monocyte cultures were infected with DEN virus type 2. Apoptosis and production of tumor necrosis factor-␣ (TNF-␣) and nitric oxide were measured in control and infected cultures. Virus was taken up by phagocytosis, but no membrane-coated pits at the virus attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 31 publications
3
66
0
2
Order By: Relevance
“…Blocking CD32 or CD64 reduced ADE by about 50 to 70% (32), indicating that both these FcR may play a role in support of the work of Littaua et al (36) but not excluding the involvement of other receptors. Further complicating the issue, monocyte infection by uncomplexed dengue virus has been reported in the range of 30 to 60% (18,58), making interpretation of the data concerning ADE challenging. Encouragingly, the finding that monocytes are nonsusceptible to FMDV IC infection is consistent with in vivo data, where no FMDV replication is detected in PBMC of infected animals (62).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking CD32 or CD64 reduced ADE by about 50 to 70% (32), indicating that both these FcR may play a role in support of the work of Littaua et al (36) but not excluding the involvement of other receptors. Further complicating the issue, monocyte infection by uncomplexed dengue virus has been reported in the range of 30 to 60% (18,58), making interpretation of the data concerning ADE challenging. Encouragingly, the finding that monocytes are nonsusceptible to FMDV IC infection is consistent with in vivo data, where no FMDV replication is detected in PBMC of infected animals (62).…”
Section: Discussionmentioning
confidence: 99%
“…We have performed some limited DV infection studies in A549 cells and observed DV-induced nuclear movement of NF-B in a much smaller percentage of cells (10%) compared with the results of the work of Chang et al (8), but within 48 h these DV-infected cells are all killed (data not shown). In our extensive studies reported herein, using in vitro cell models representing DV infection of macrophages and liver cells, two important primary cell targets for DV in vivo, we did not observe DV induction of nuclear NF-B movement but instead observed DV blockade of TNF-␣-stimulated NF-B activation, at a time of established DV infection but with very little (3 to 10%) apoptosis (16,42). Thus, while high-level DV infection of cell lines may activate NF-B and induce apoptosis, during active DV replication in primary MDM or hepatoma cell lines DV does not activate NF-B and in fact has the capacity to prevent its activation by TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ is released from monocyte-derived macrophages (MDM) after DV infection, and the peak of this release coincides with the peak of virus production in vitro (7,16). Other cells of the immune system such as B and T cells that functionally interact with monocytes and macrophages during viral infection can also release TNF-␣ when exposed to DV (35)(36)(37).…”
mentioning
confidence: 99%
“…4A and B). It has been reported that human monocytes infected by DV produce TNF-␣ (3,5). Sensitized T cells from dengue patients also produce TNF-␣ in culture upon restimulation (7,20).…”
Section: Discussionmentioning
confidence: 99%